Role of Culture in Engaging Consumers in Organizational Social media Posts. Issue 4 (1st October 2020) - Argyris, Young Anna; Wang, Yaqian; Muqaddam, Aziz
ABSTRACT: Despite the wide consensus on the importance of culture in the deployment and use of information systems, very few studies have investigated whether and how organizations should incorporate the societal culture in their social media (SM) content strategy to increase consumer engagement. Recently, Chinese organizations have succeeded in engaging consumers using their local applications, such as WeChat and Weibo, calling for research on the role of Chinese cultures in such successes. Our research objectives are therefore to identify how organizational SM content strategy manifests and what makes SM content engaging in Chinese cultural contexts. As a theoretical framework, we chose the typology of symbolic-utilitarian message appeals and applied it to the six prominent areas of consumer engagement. We then analyzed Chinese organizations' preferences for message appeals for each of the six areas using thematic analyses. The results of our analyses demonstrate the roles of Guanxi (interpersonal relationships), the changing nature of Mianzi (saving face), and the emergence of sympathy appeals in Chinese firms' choice of SM content strategies. Based on these findings, we propose an expanded conceptual framework that encompasses cultural perspectives in organizational SM content strategies.